2018
DOI: 10.1111/lam.12999
|View full text |Cite
|
Sign up to set email alerts
|

AttenuatedSalmonella VNP20009 mutant(ΔhtrA) is a promising candidate for bacteria-mediated tumour therapy in hosts with TNFR1 deficiency

Abstract: VNP20009 is attenuated Salmonella with a good safety widely used for tumour-targeting bacterial therapies. Little is known about its toxicity in hosts with low immunity. This study is the first systemically comparative analysis of their toxicity of VNP20009 and its mutant ΔhtrA in TNFR1-KO mice. Research on toxicity of tumour-targeting Salmonella in mice with immunodeficiency can facilitate the optimization of bacterial therapies with reduced adverse effects in future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Although viruses have been utilized for genetic therapeutics to permanently overexpress protein drugs or interfering RNAs in target cells 5,6 , the utility of viruses is largely limited by their rapid spread, difficulty to eliminate and potential to cause serious infections. Bacteria, another group of broadly used microorganisms, are relatively manipulable and safe, because they are easy to be modified genetically and can be controlled by antibiotics 79 . More importantly, various bacterial species are able to colonize specific body sites of mammalian hosts, for example the gut or the skin, as well as disease sites including abscesses and tumor tissues 8,1014 .…”
Section: Introductionmentioning
confidence: 99%
“…Although viruses have been utilized for genetic therapeutics to permanently overexpress protein drugs or interfering RNAs in target cells 5,6 , the utility of viruses is largely limited by their rapid spread, difficulty to eliminate and potential to cause serious infections. Bacteria, another group of broadly used microorganisms, are relatively manipulable and safe, because they are easy to be modified genetically and can be controlled by antibiotics 79 . More importantly, various bacterial species are able to colonize specific body sites of mammalian hosts, for example the gut or the skin, as well as disease sites including abscesses and tumor tissues 8,1014 .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, many organisms have shown prominent anti-tumor effects in various cancer models. These include Listeria monocytogenes, Salmonella typhimurium and many other programmable bacteria [19][20][21][22][23][24][25], the oncolytic virus Talimogene laherparepvec [26], cowpea mosaic virus [27][28][29][30], yellow fever vaccine 17D [31] and the artificial attenuated parasite Toxoplasma gondii [32][33][34][35][36][37], all of which have been reported to be able to inhibit the growth or metastasis of tumors as well as improve prognosis. Genetic manipulation enables the generation of avirulent or attenuated microorganisms that can induce powerful immune responses, making them effective immune-stimulating anti-tumor agents.…”
mentioning
confidence: 99%
“…Recently, VNP20009 has been sequenced for other genes to improve tumor targeting. Aside from the known purI and msbB gene deletions, other mutations have also been found, including a 108-kb Suwwan deletion, 50 nonsynonymous SNPs, a purM deletion and a derivative ∆htrA 29, 30. More research is needed to prove their effectiveness and stability.…”
Section: S Typhimurium Laboratory Strains For Cancer Therapymentioning
confidence: 99%